Implantación del sistema de contabilidad de costos por órdenes de produccion, aplicada a la fabrica de calzado Deyf Faerma, del canton Chordeleg, provincia del Azuay; periodo julioseptiembre de 2013 - Piedra Ojeda, Gabriela Katherine (2014)
In this thesis entitled "Implementation of Cost Accounting System for Production Orders, applied to Deyf Faerma Shoe Factory, Chordeleg Canton, Azuay Province; July-September period of 2013, "has fully complied with the development of objectives, the same that is based on the work of literature and field research as well as input from lessons learned in the company and tips counseling-supervision of the Director of Thesis. It is also important to note that an analysis of manufacturing overhead, variable overhead, fixed overhead costs, finished goods inventory and costing of materials and labor used in production, is presented for this method is used average cost. Similarly, the financial statements, objectives, constraints, features, rules and classes presentation of financial statements, for this type of business, emphasizing the production control are presented. As a result of this thesis is concluded that the manager must continue collecting all the information generated in the factory for all these documents can continue this proposal to take an accounting system to determine actual values of the financial situation of the company and thus I found a very interesting and usable for professional branch in me that I will perform it.